Phosphate source induced rapid synthesis of urchin-like hydrated GdPO4:Eu3+ nanoparticles: Imaging and drug delivery in A549 cell line. Issue 16 (15th August 2022) - Varaprasad, Ganji Lakshmi; Lee, Hoomin; Kim, Suheon; Kim, Eunsu; Pavitra, Eluri; Valluru, Neeraja; Han, Young-Kyu; Raju, Ganji Seeta Rama; Huh, Yun Suk
Abstract: Energy and environmental concerns are increasing owing to the increased consumption of resources. To help solve the energy crisis and contribute to protecting our environment, this study aimed to develop a fast and eco-friendly method of synthesis. We propose a H3 PO4 assisted fast synthesis technique for developing urchin-like GdPO4 ·xH2 O:5Eu 3+ nanoparticles. First, Gd(OH)CO3 :5Eu 3+ nanospheres with sizes of about 60 nm were developed using urea-based homogeneous precipitation. These nanospheres were utilized as the Gd 3+ source and sacrificial templates in the formation of urchin-like GdPO4 .xH2 O:5Eu 3+ nanoparticles, where the Kirkendall effect takes place during hydrothermal synthesis. The structural properties confirmed the existence of the H2 O phase in the GdPO4 :5Eu 3+ nanoparticles. The synthesized urchin-like GdPO4·xH2 O:5Eu 3+ nanoparticles exhibited excellent photoluminescence in the reddish-orange region upon excitation by near-UV excitation wavelengths. These urchin-like nanoparticles demonstrated effective penetration in lung cancer cells by exhibiting luminescence from both the cytoplasm and nucleoplasm. The conjugation of doxorubicin with urchin-like GdPO4 ·xH2 O:5Eu 3+ nanoparticles helped to realize efficient antitumor activity against lung cancer.